2021
DOI: 10.3390/ijerph182413149
|View full text |Cite
|
Sign up to set email alerts
|

Accept Anxiety to Improve Sleep: The Impact of the COVID-19 Lockdown on the Relationships between Mindfulness, Distress, and Sleep Quality

Abstract: It has been recently proposed that mindfulness can improve sleep quality through the mediating role on psychological distress and that acceptance may play a pivotal role in mindfulness beneficial effects. The aim of the present work was to understand the effects of the COVID-19 lockdown on dispositional mindfulness, sleep, and distress, and on their relationships. In particular, we wanted to test the hypothesis that the detrimental effects of lockdown on sleep depended on mindfulness and distress (including an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 40 publications
11
27
1
Order By: Relevance
“…These findings were further confirmed during the third lockdown that occurred in Italy the following spring (from 15 March to 21 June 2021). On one hand, Conte et al [8] demonstrated the presence of disrupted sleep and increased poor subjective sleep, similar to what had been reported in the previous waves [3][4][5][6][7]. On the other hand, the authors also described that sleep duration was in the normal range, suggesting that the (repetitive) experience of lockdown mainly affected the quality rather than the quantity of sleep.…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…These findings were further confirmed during the third lockdown that occurred in Italy the following spring (from 15 March to 21 June 2021). On one hand, Conte et al [8] demonstrated the presence of disrupted sleep and increased poor subjective sleep, similar to what had been reported in the previous waves [3][4][5][6][7]. On the other hand, the authors also described that sleep duration was in the normal range, suggesting that the (repetitive) experience of lockdown mainly affected the quality rather than the quantity of sleep.…”
Section: Introductionsupporting
confidence: 68%
“…However, Simione et al [17] challenged this theory, by demonstrating that acceptance was the only predictor of several benefits of mindfulness, including those regarding sleep quality. Interestingly, Mirolli et al [5] recently confirmed these findings in a longitudinal study by comparing mindfulness traits, general distress, and sleep quality, before and during the first Italian lockdown. In particular, this study demonstrated that acceptance (and not monitoring), influenced sleep through the mediating role of anxiety [5,17].…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations